2020
DOI: 10.1002/nau.24416
|View full text |Cite
|
Sign up to set email alerts
|

Do voiding urodynamic parameters predict the success of adjustable transobturator male system (ATOMS) to treat postprostatectomy urinary incontinence?

Abstract: Objective To evaluate whether urodynamic voiding risk factors can be predictive of failure of postprostatectomy urinary incontinence (PPI) treatment with adjustable transobturator male system (ATOMS). Materials and Methods We carried out a longitudinal study on 77 males treated for PPI with ATOMS. Patients were submitted preoperatively to a urodynamic study. The postoperative outcome was checked by pad‐test. Treatment success was defined as daily pad‐test below 10 mL. Statistical analysis used were Fisher exac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…However, unlike this, a study showed that patients with higher BOOI have less chance of being cured of their incontinence after ATOMS implantation. 22 Furthermore, most studies were unable to diagnose a BOO because they used BOOI, a parameter with an indeterminate region of values. This drawback does not occur with the URA parameter whose normal values are well determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike this, a study showed that patients with higher BOOI have less chance of being cured of their incontinence after ATOMS implantation. 22 Furthermore, most studies were unable to diagnose a BOO because they used BOOI, a parameter with an indeterminate region of values. This drawback does not occur with the URA parameter whose normal values are well determined.…”
Section: Resultsmentioning
confidence: 99%
“…Utomo et al 21 measured BOOI before and after implantation of the volume adjustable balloons proACT, and they observed a significant increase in BOOI only in patients with successful outcome. However, unlike this, a study showed that patients with higher BOOI have less chance of being cured of their incontinence after ATOMS implantation 22 . Furthermore, most studies were unable to diagnose a BOO because they used BOOI, a parameter with an indeterminate region of values.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, adjustable slings that need no manipulation to overcome cognitive and dexterity issues and offer results approaching or even overtaking those of AUS are increasingly used 25–28 . Moreover, optimal patient selection based on functional voiding parameters may further improve the functional outcomes of the ATOMS device 29 . However, there is very limited experience upon the secondary use of ATOMS 30 .…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] Moreover, optimal patient selection based on functional voiding parameters may further improve the functional outcomes of the ATOMS device. 29 However, there is very limited experience upon the secondary use of ATOMS. 30 Also, its explant rate is variable in the literature and ranges between 2% and 30.5%, according to follow-up length and the proportion of patients included with device generations other than the actual silicone-covered scrotal port (SSP).…”
Section: Discussionmentioning
confidence: 99%
“…The ATOMS device is also advantageous over other adjustable systems, both for a diminished rate of complications compared to the male REEMEX system [6] and also for Uro 2021, 1 46 increased effectiveness and durability compared to ProACT [7]. However, its mode of action is not well understood and analyses using urodynamic studies are scarce [8]. Our hypothesis is that the compression produced by the cushion filling produces a stretching effect on the bulbar urethra that increases urethral resistance and enhances the residual sphincteric activity, and also that the different responses to serial filling of the cushion intraoperatively after ATOMS placement could help to define the patients with the best postoperative results.…”
Section: Introductionmentioning
confidence: 99%